2013
DOI: 10.1128/jvi.02079-12
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mucosal Inflammation on Oral Simian Immunodeficiency Virus Transmission

Abstract: dMucosal tissues are the primary route of transmission for most respiratory and sexually transmitted diseases, including human immunodeficiency virus (HIV). There is epidemiological evidence that genital mucosal inflammation leads to enhanced HIV type 1 (HIV-1) transmission. The objective of this study was to assess the influence of periodontal inflammation on oral HIV transmission using a nonhuman primate model of teeth ligature-induced periodontitis. Simian immunodeficiency virus (SIV) was nontraumatically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…This approximates what was seen in the vaginal transmission studies, with establishment of viral replication at mucosal sites and virus dissemination into the draining lymphatics (Wood et al, 2013). Additionally, a pro-inflammatory response at the mucosa has been reported during oral SIVmac transmission in RMs, which may facilitate target cell recruitment to the site of infection to support early virus replication (Giavedoni et al, 2013). …”
Section: Characteristics Of Horizontal and Vertical Transmission Tmentioning
confidence: 99%
“…This approximates what was seen in the vaginal transmission studies, with establishment of viral replication at mucosal sites and virus dissemination into the draining lymphatics (Wood et al, 2013). Additionally, a pro-inflammatory response at the mucosa has been reported during oral SIVmac transmission in RMs, which may facilitate target cell recruitment to the site of infection to support early virus replication (Giavedoni et al, 2013). …”
Section: Characteristics Of Horizontal and Vertical Transmission Tmentioning
confidence: 99%
“…These investigators identified an increased risk in SHIV infection in treated macaques, which likely resulted in both increased access to underlying target cells, recruitment of additional target cells to the site of inflammation as well as an activation of the target cells themselves (87). In contrast, a study from our laboratory experimentally induced gingival inflammation in adult rhesus macaques that mimicked the mild to moderate gingivitis common in humans (238). This was accomplished by tying silk ligatures around the base of the teeth and softening the macaque’s food with water.…”
Section: Inflammation and Oral Hiv/siv Susceptibilitymentioning
confidence: 99%
“…This treatment induced strong upregulation of multiple inflammatory markers in the oral tissue, including IL6, IL8, and IL18. Macaques were then orally exposed to repeated low dose challenge of SIVmac251 and, surprisingly, the rate of SIV transmission was similar in the gingivitis and control macaque groups, although an increase in the number of viral variants that establish the SIV infection was observed (238). One interesting distinction that may explain the different findings in these two studies is that while gingivitis does result in inflamed mucosa it does not necessarily compromised the mucosal barrier, which likely occurred with acetic acid treatment, potentially explaining the increased susceptibility in the acetic acid treated animals but not in the gingivitis animals.…”
Section: Inflammation and Oral Hiv/siv Susceptibilitymentioning
confidence: 99%
“…Depending on the exact site of viral transmission, there are various barriers to infection and target cell availability. Currently, there are limited NHP models dedicated to oral transmission [49,50]. Additional studies will be needed to expand our understanding of oral transmission.…”
Section: Nhp Models Of Transmissionmentioning
confidence: 99%